Virtual Saviours: Digital games and anti-trafficking awareness-raising - O’Brien, Erin; Berents, Helen (Anti-Trafficking Review, 2019)
In recent years, digital games have emerged as a new tool in human trafficking awareness-raising. These games reflect a trend towards ‘virtual humanitarianism’, utilising digital technologies to convey narratives of suffering with the aim of raising awareness about humanitarian issues. The creation of these games raises questions about whether new technologies will depict humanitarian problems in new ways, or simply perpetuate problematic stereotypes. This article examines three online games released in the last five years for the purpose of raising awareness about human trafficking. In analysing these games, we argue that the persistent tropes of ideal victims lacking in agency continue to dominate the narrative, with a focus on individualised problems rather than structural causes of human trafficking. However, the differing approaches taken by the games demonstrate the potential for complexity and nuance in storytelling through digital games.